Icariin accelerates cartilage defect repair by promoting chondrogenic differentiation of BMSCs under conditions of oxygen‐glucose deprivation. Issue 1 (3rd December 2021) - Tang, Wang; Zhang, Hongyi; Liu, Donghua; Jiao, Feng
Abstract: This study explored the role played by combined ICA and bone mesenchymal stem cells (BMSCs) in repairing rabbit knee cartilage defects. Firstly, rabbit BMSCs were isolated and used to construct an in vitro cellular model of oxygen‐glucose deprivation/reoxygenation (OGD/R). Subsequently, ICA processing, Alcian blue staining, immunofluorescence and Western blot studies were performed to evaluate the ability of BMSCs to display signs of chondrogenic differentiation. Furthermore, a rabbit knee cartilage injury model was established in vivo. International Cartilage Repair Society (ICRS) macroscopic evaluations, H&E, Alcian blue and EdU staining, as well as immunohistochemistry, were analysed cartilage repair and pathological condition of the knee cartilage tissue. Our in vitro results showed that ICA promoted the chondrogenic differentiation of BMSCs, as well as aggrecan (AGR), bone morphogenetic protein 2 (BMP2) and COL2A1 protein expression in BMSCs. In vivo experiments showed that rabbits in the BMSCs or ICA treatment group had higher ICRS scores and displayed a better restoration of cartilage‐like tissue and chondrocyte expression on the surface of their cartilage defects. In conclusion, ICA or BMSCs alone could repair rabbit knee cartilage damage, and combined treatment with ICA and BMSCs showed a better ability to repair rabbit knee cartilage damage.